Titik Equilibrium Bebas dari Penyebaran Hoax Pemilu Lewat Media Sosial Tiktok - Anna Angela Sitinjak; Switamy A. Purba; Ferdinan Rinaldo Tampubolon; Dimas Frananta S; Naqasya Asyrori Sidabutar (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2024)
Election issues are sensitive information among the society because they relate to people's survival in terms of work, economy and education. Election hoaxes where information whose truth cannot be ascertained becomes a weapon used by certain parties to bring down political opponents. Social media such as TikTok is a media that is often used to spread hoaxes because TikTok social media users come from various ages and there is no distance or time between users. In this paper, a mathematical model is presented to see how the equilibrium point is to be free from hoax based on the basic reproduction number R0. The spread of hoaxes on social media occurs if R0 > 1 and does not occur if R0 < 1. The model approach used is the SEIR mathematical model because it is seen that there are people who receive hoax videos (exposed) and then spread them without finding out the truth (infected), and users with this condition it needs to be recovered. The method used in this research is a literature review. The results obtained show that the mathematical model presented shows that the basic reproduction number R0 is zero (R0 < 1). This means that there will be no spread of election hoaxes